A Study of Effective Team Building in Relation to Organizational Culture and Organizational Climate in Universities in Delhi. (July 2014) - Banerjee, Priyanka
Educational organizations are facing severe problems in terms of competition, quality degradation and deteriorating standards. There is a need to identify, define, develop strategy, initiate action and solve the problem. The present research holds significance in the rapidity of changing environment that affects our educational organizations today, which need to be continuously assessed for future requirements so that they can meet the demands of the changing world and remain inqstitutes of excellence by maintaining their standards. To establish the importance of organizational development (OD) interventions in the education arena was the primary aim of conducting this research so that education sector too is able to reap benefits as all others, be it industrial, business, scientific, etc. Descriptive research method was employed wherein three variables—organizational culture, organizational climate and effective team building—were juxtaposed between one central and one state university in New Delhi. Sample was drawn from 10 academic departments of the universities and 10 teachers from each department; thus, the total sample size comprised 100 teachers. Results revealed that central universities have bureaucratic and autocratic culture with moderately favourable organizational climate and team effectiveness being high, while state university was diametrically opposite with technical, entrepreneurial culture, more favourable organizational climate and very high team effectiveness. This study proves to be an eye-opener for educationists, administrators, policy planners and academicians so as to help them understand the principles, practices, diagnose problems and bring about a paradigmatic shift in policy structures by accommodating the innovative changes for building empires out of organizations.